2021
DOI: 10.1177/21514593211058969
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Hip Fractures: Other Fragility Fractures’ Associated Mortality, Functional and Economic Importance: A 2-year-Follow-up.

Abstract: Background Hip fractures are well researched in orthogeriatric literature. Equivalent investigations for fragility-associated periprosthetic and periosteosynthetic femoral, ankle joint, pelvic ring, and rib fractures are still rare. The purpose of this study was to evaluate mortality, functional outcome, and socioeconomic parameters associated to the upper-mentioned fragility fractures prospectively in a 2-year follow-up. Methods Over the course of a year, all periprosthetic and periosteosynthetic femoral frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Even if not all abilities assessed by the Barthel Index are related to the functionality of the hip joint, experience shows that limited mobility and functionality of the lower extremity affects the patient in many ways and in other areas of life. Data shows that limited mobility aggravates comorbidities and increases mortality [9][10][11]. Advanced age, low preoperative functional status, ability to participate in physical therapy and blood loss appear to be particularly outcome-relevant in the management of hip fractures [12].…”
Section: Introductionmentioning
confidence: 99%
“…Even if not all abilities assessed by the Barthel Index are related to the functionality of the hip joint, experience shows that limited mobility and functionality of the lower extremity affects the patient in many ways and in other areas of life. Data shows that limited mobility aggravates comorbidities and increases mortality [9][10][11]. Advanced age, low preoperative functional status, ability to participate in physical therapy and blood loss appear to be particularly outcome-relevant in the management of hip fractures [12].…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of postoperative functional decline in the elderly is higher than that in younger generations 3. Decreased patient function leads to increased caregiver burden and social costs 4–7. In addition, an interview survey of elderly people suffering from serious illnesses reported that about 75% of patients who are expected to have severe functional deterioration do not want treatment even if the burden is light 8.…”
mentioning
confidence: 99%